2017
DOI: 10.15171/jcs.2017.017
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Happiness Training Based on Fordyce Model on Perceived Stress in the Mothers of Children with Cleft Lip and Palate

Abstract: Introduction: A child afflicted with facial deformities such as cleft lip and palate usually affects their parents, because of difficulties in nutrition, speech, aesthetics and social connections, and also imposing a lot of stress on them. The aim of this study was to investigate the effects of a happiness program on the perceived stress in the mothers of children with cleft lip and palate. Methods: This study was a quasi-experimental study in which 64 mothers of children with cleft lip and palate were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
1
16
1
Order By: Relevance
“…24 Brazil is internationally recognized as the country with the highest rates of cesarean sections in the world, and approximately 40% in the public sector and 80 to 95% in the private sector. 25 In respect to the Apgar score at the 1 st and the 5 th minutes, no studies were found that would confirm the findings of the present study. It is known that babies who presented evaluation by the Apgar score lower than seven in the 1 st and the 5 th minutes revealed more chances to evolve to the death of that babies with scores above eight, 22 reinforcing the need of offering assistance quality at the moment of birth, aiming at the reduction of risk of death of babies with cleft lip and/or cleft palate.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…24 Brazil is internationally recognized as the country with the highest rates of cesarean sections in the world, and approximately 40% in the public sector and 80 to 95% in the private sector. 25 In respect to the Apgar score at the 1 st and the 5 th minutes, no studies were found that would confirm the findings of the present study. It is known that babies who presented evaluation by the Apgar score lower than seven in the 1 st and the 5 th minutes revealed more chances to evolve to the death of that babies with scores above eight, 22 reinforcing the need of offering assistance quality at the moment of birth, aiming at the reduction of risk of death of babies with cleft lip and/or cleft palate.…”
Section: Discussioncontrasting
confidence: 60%
“…Low birth weight pointed out as a risk factor also reinforces the findings of the literature, a fact that can be explained by the birth route is chosen, because the majority of babies with cleft lip and/or cleft palate born of scheduled cesarean births, which means that not always are already ripe for the birth, being removed from the intrauterine life before the stage of weight gain. 25,26 Finally, it is worth noting that a multi and interdisciplinary team, with a view to ensuring that it can enjoy all the features of treatment available, must follow the development of a child with cleft lip and/or cleft palate. It is important to consider that, once the treatment has started, properly and early, the chances of the baby with cleft lip and/or cleft palate has a development with quality of life are amplified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum total self-esteem score is 50. Validity and reliability of CSEI have been confirmed in previous studies (r=92%) (Hemati et al 2017). In addition, Delaram et al estimated the reliability of this tool as 93% (Delaram et al 2012).…”
Section: Study Measuresmentioning
confidence: 60%
“…Studies explored a number of AAHCs; six focused on atopic eczema (Chinn et al, 2002;Grillo et al, 2006;Morawska et al, 2016Morawska et al, , 2017aMorawska et al, & 2017bSanter et al, 2014) et al, 2002 & 2006), three on cleft lip and/or palate (Hemati, Abbasi, Oujian, & Kiani, 2017;Hemati, Abbasi, Paki, & Kiani, 2017;Pelchat et al, 1999) and one on burn injuries (Sveen et al, 2017).…”
Section: Study Characteristicsmentioning
confidence: 99%